Pengembangan alat sterilisasi mikroorganisme dan pelaksanaan disinfeksi berkala sebagai upaya untuk memutus rantai penularan covid-19 - Irham Fadlika; Aripriharta Aripriharta; Irawan Dwiwahyono; Muhammad Rizal Andriansyah; M. Ricko Gunawan; Eka Mistakim; Ach. Syahrudin Fakhri (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Covid-19 is a malignant virus that has spread throughout the world, including Indonesia. In Indonesia alone, Covid-19 has proliferated to 502 districts and cities in 34 provinces, including Harjokuncaran Village, Sumbermanjing Wetan District, Malang Regency. Two main issues, community economy problem and inadequacy of health facilities to fight Covid-19, are addressed and mitigated in this work. We offer some solutions, including the production of a disinfectant sprayer and a call to carry out sterilization activities in public places together. The realization of this community service program uses the Dignan method which includes five stages. The initial implementation of this activity, which was carried out on October 5, 2020 has gone smoothly with the help of the community, while the tools that have been fully provided to the residents are used to carry out sterilization activities on a regular basis. Six months after the activity, we evaluated the success of this endeavor. There are three indicators of success in this activity, namely a recapitulation of monthly spraying activities from October 2020 - March 2021, the addition of positive cases of Covid-19, and how much knowledge of residents about the importance of spraying disinfectant activities